Effect of liquid oxy-nitriding at various temperatures on wear and molten aluminum corrosion behaviors of AISI H13 steel. (January 2021) - Chen, Guang; Wang, Jun; Wang, Danqi; Xue, Ling; Zeng, Bo; Qin, Bingchao; Tang, Zhenghua
Highlights: Temperature of LON treatments influences the microstructure of modified surface. Both high-hardness compound layers and lubricated oxide films are good for wear. Nitriding layer has a certain hindering effect on the formation of IMCs. Fe3 O4 film promotes corrosion behaviors transform from dissolution into oxidation. LON treatments are promising for combating dissolution corrosion of liquid metals. Abstract: In this study, liquid oxy-nitriding (LON) at different temperatures (430 °C, 450 °C, 470 °C) was employed on the AISI H13 steel. Effects of LON on wear and molten aluminum corrosion of AISI H13 steel were investigated. LON treatments significantly improved wear resistance due to synergy between high-hardness nitriding layer and lubricating oxide film. Molten aluminum corrosion resistance was also improved, especially by LON 470 treatment. Fe3 O4 film and nitriding layer on LON 470 transformed the corrosion mechanisms from dissolution into oxidation. Therefore, LON process may be a choice for combating the dissolution corrosion of liquid metals.